2017
DOI: 10.1016/j.jtbi.2017.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Simple mechanical cues could explain adipose tissue morphology

Abstract: The mechanisms by which organs acquire their functional structure and realize its maintenance (or homeostasis) over time are still largely unknown. In this paper, we investigate this question on adipose tissue. Adipose tissue can represent 20 to 50% of the body weight. Its investigation is key to overcome a large array of metabolic disorders that heavily strike populations worldwide. Adipose tissue consists of lobular clusters of adipocytes surrounded by an organized collagen fiber network. By supplying substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…A good biological example for this kind of assumption would be the process of growth of adipose tissue studied in [26]. It takes about 100 days for a nascent adipocyte to grow to its maximum size, while for the extracellular matrix complete remodeling takes up to 15 days.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…A good biological example for this kind of assumption would be the process of growth of adipose tissue studied in [26]. It takes about 100 days for a nascent adipocyte to grow to its maximum size, while for the extracellular matrix complete remodeling takes up to 15 days.…”
Section: Preliminariesmentioning
confidence: 99%
“…Nevertheless, one common feature of these systems is the strong coupling between the dynamical evolution of the individual agents (cells or monomers, for instance) with that of the network mediating their interactions. The mathematical modeling of this strongly coupled dynamics is a challenging task (see, for example, [26]) but it is a necessary step toward building more complete models of complex biological or social phenomena.…”
mentioning
confidence: 99%
“…(i) Introduction of new fibers/cells. To create a simulation framework that addresses the mechanical features of adipogenesis and homeostasis, a 2D individual based model (IBM) was introduced in [46]. Here, we use the same framework to model tissue repair after injury.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The choice of fiber length and width is motivated by studies of [57], where it is shown that the collagen fibers are organized into bundles of collagen fibrils the width of which varying from 1 to 20µm depending on tissues and organs. In order to enable the fibers to bend around the cells, the fiber elements are chosen to be 20µm wide and 60µm long (the adipocyte diameter being 60µm, see [46]). The model parameters used for the simulations are given in table 1.…”
Section: Biological Relevance Of the Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation